A Pd-catalyzed route to carborane-fused boron heterocycles - Zhu, Mengjie; Wang, Puzhao; Wu, Zhengqiu; Zhong, Yangfa; Su, Laiman; Xin, Yuquan; Spokoyny, Alexander M; Zou, Chao; Mu, Xin (Chemical science (Cambridge), 2024)
Due to the expanding applications of icosahedral carboranes in medicinal and materials chemistry research, their functionalizations have become one of the central themes in boron-rich cluster chemistry. Although several strategies for incorporating nitrogen-containing nucleophiles on a single boron vertex of the icosahedral carboranes (C 2 B 10 H 12 ) have been developed, methods for preparing clusters with vicinal B-N moieties are still lacking. The steric bulk of icosahedral carboranes and disparate electronic and steric nature of the N-containing groups have rendered the vicinal diamination challenging. In this article, we show how a developed Pd-catalyzed process is used to incorporate an array of NH-heterocycles, anilines, and heteroanilines with various electronic and steric profiles onto the vicinal boron vertices of a meta -carborane cluster via sequential or one-pot fashion. Importantly, oxidative cyclizations of the cross-coupling products with indoles and pyrroles appended to boron vertices generate a previously unknown class of all-boron-vertex bound carborane-fused six- and seven-membered ring heterocycles. Photophysical studies of the meta -carborane-fused heterocycles show that these structures can exhibit luminescence with high quantum yields and are amenable to further manipulations. A Pd-catalyzed cross-coupling system has been developed to achieve vicinal diamination of 9,10-dibromo-carborane with NH-heterocycles and anilines. These products can be further converted to carborane-fused six- and seven-membered heterocycles.